Report on the Annual Survey of Industries 1989-90 Andhra Pradesh - Planning Commission (Planning Commission, 1989)
The Annual Survey of Industries (ASI ) is the principal source of industrial statistics in India. It provides statistical Information to assess and evaluate, objectively and realistically, the changes in the growth, composition and structure of the organised manufacturing sector comprising activities related to manufacturing processes, repair services, generation, transmission etc. of electricity, gas and water supply and cold storage. Industrial sector occupies an important position in the Indian economy and has a pivotal role to play in the rapid and balanced economic development.
Directorate of Economics and Statistics, Government of Andhra Pradesh